Oocytes as Alternative to Embryos in Cryopreservation Applied in Assisted Reproductive Technologies - Buderatska, Natalia O.; Petrushko, Maryna P. (Problems of Cryobiology and Cryomedicine, 2016)
Application of the cryobiological techniques in reproductive medicine enables the successful cryopreservation of gametes and embryos of the patients undergoing treatment for infertility. The scientific publications describe the approaches to cryopreservation of oocytes and embryos, but the comparative analysis of efficiency of using these programs is not available. In the paper we described the basic embryological and clinical parameters (frequency of fertilization and blastocyst formation; the average number of embryos per a transfer into the uterus, the pregnancy rate, implantation rate, number of multiple pregnancies) after cryopreservation of either oocytes or embryos. There were examined the oocytes at metaphase II stage of meiosis and human embryos of the fifth day of development (the blastocyst stage). It has been demonstrated that oocyte cryopreservation by vitrification did not affect their fertilizing capacity, but the rate of blastocyst formation was significantly lower than those of freshly isolated oocytes. Basic clinical cure rates were comparable in the groups with vitrification of oocytes and embryos, as well as in the control. The cryopreservation of oocytes has been found as an alternative to preservation of embryos at low temperatures. Probl Cryobiol Cryomed 2016; 26(4):375–382